INFLUENCE OF MICROBIOLOGICAL PREPARATIONS ON PHYSIOLOGICAL PROCESSES OF FORMATION OF GRAIN PRODUCTIVITY OF WINTER WHEAT - Vinyukov, O.; Chuhrii, H.; Poplevko, V.; Szulc, P.; Sknypa, N. (Scientific Progress & Innovations, 2022)
The article defines the influence of microbiological preparations on the physiological processes of the formation of grain productivity of winter wheat. The impact of climatic changes depending on the zone of winter wheat cultivation is determined. The study established that seed inoculation with microbiological preparations improved the course of particular physiological processes, especially the accumulation of chlorophyll in leaves. It was found that the autumn vegetation of winter crops in the years of research contributed to the increase in chlorophyll content in the vegetative parts of plants. At the end of the autumn growing season, all options where seed inoculation had been used provided an increase in the chlorophyll content compared to the control from 0.3 to 0.6 mg/g (automated calculation system). During the recovery of vegetation, the chlorophyll content decreased compared to the autumn indicators. It was found that the use of microbiological preparations in winter wheat cultivation technologies helps to increase the supply of nutrients to plants, which stimulates the development of plants during the growing season, and, as a result, increases the parameters of the crop structure. Variants with the spraying of crops affected the length of the ear, provided an increase compared to the control variant by 4.1 % (due to spraying crops with GumiFriend in the fall at the beginning of the tillering phase) and by 6.9 % (when spraying crops with this preparation in the spring in the phase of emergence into the tube ). It is proved that the level of grain productivity of plants is a significant manifestation of the influence of the proposed element of the technological process of growing crops. It was established that during the years of research, the most significant yield increase was due to the inoculation of seeds with the Melanoriz preparation (12.49 % under the control). The addition of HelpRost inoculant to this preparation increased the yield compared to the control by 6.25 %, and its combination with GumiFriend – by 7.37%.